Zoonotic Importance and Prevalence of Toxocara spp among Pets in Tripoli, Libya - Mansour L1*, Gerish E2, Al-Toome S1 (AlQalam Journal of Medical and Applied Sciences, 2017)
Background and Purpose: The pets are increasingly considered a member of the family, physical contact is very common and a diverse range zoonotic infections, including parasitic, bacterial, fungal and viral diseases are capable of being transmitted from dogs and cats to humans by direct contact with them. Studies on dog and cats endoparasites in Tripoli, Libya are limited and very little information is available about the prevalence and risk factors associated with parasites occurrence. This information is important in evaluating and recommending parasite control measures in companion animals health and welfare programmes. Hence this cross-sectional study was conducted to determine the prevalence of Toxocara spp in faecal samples of owned dogs and cats. Demographic data on age, gender, breed and purpose deworming status among pets in Tripoli, Libya was also taken. Methods: Study was carried out in the period from 4th of October 2009 to 18th of April 2011, 73 dogs and 51 cats from different localities in study area, were investigated. The animals were examined during their visits to private and governmental veterinary clinics for routine procedures such as check-up or vaccination. All animals were subjected to clinical examination and their general condition were evaluated. A structured questionnaire was designed to gather information on pet ownership, management and related risks. The faecal samples were collected from all investigated pets, then processed and examined by qualitative floatation coprological analysis, as described in the literatures. Egg identification was based on morphological characteristics (shape and structure of shell) and measurements. Results: The overall prevalence of Toxocara canis was 15% in the dogs, meanwhile 3.9% of the cats were infected with Toxocara cati. Moreover the prevalence in dogs subjected to a deworming regimen was 6%. Whereas the prevalence in cats subjected to a deworming regimen was 0%. The findings revealed that there is no significant statistical association between the gender and breed with the infection in both dogs and cats. The age of the dogs had a considerable influence on prevalence, with a much higher proportion of younger dogs (1 - 6 months old) being infected. Conclusion: Considering the zoonotic potential of the estimated parasite species, the results are very important for public health. The priorities of preventive strategies include the awareness of society and in particular pet owners consisting of avoid contamination of the environment with Toxocara spp eggs is recommended, and also the close collaboration between the veterinary and human health services. Other studies are required to assess the efficacy of applied antiparasitic drugs, as well as to the indiscriminate use of broad spectrum anthelmintics must be challenged before serious parasite resistance in dogs and cats becomes common place.